1990
DOI: 10.1177/144078339002600102
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Ideology of Motherhood: Leisure as Resistance

Abstract: The structural view of power in feminist analysis to date has discouraged women as victims from thinking that anything they do at an individual level can be effective in the gender struggle. This article presents a view of power that incorporates resistance. Leisure as resistance for mothers of first babies is explored. The intersection of two contradictory discourses: the discourse on motherhood and that on human rights allows these mothers to transform some repressive aspects of motherhood. The vehicle is le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
3

Year Published

1994
1994
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(39 citation statements)
references
References 12 publications
0
36
0
3
Order By: Relevance
“…Many scholars have recognized that LTPA, while a relative site for freedom, pleasure, choice, and personal growth, offers the potential for resistance as individuals find personal empowerment through challenging power structures embedded in social life (Dionigi, 2002;Green, 1998;Wearing, 1990). For instance, it has been suggested that although women are variously constrained in their LTPA by hegemonic power structures, gender stereotyping and an ethic of care linked to marriage and motherhood (Deem & Gilroy, 1998;Henderson & Allen, 1991), they are also capable of resisting these normalizing discourses (Foucault, 1980;Rojek, 1989;Wearing, 1998).…”
Section: Ltpa and Resistancementioning
confidence: 99%
“…Many scholars have recognized that LTPA, while a relative site for freedom, pleasure, choice, and personal growth, offers the potential for resistance as individuals find personal empowerment through challenging power structures embedded in social life (Dionigi, 2002;Green, 1998;Wearing, 1990). For instance, it has been suggested that although women are variously constrained in their LTPA by hegemonic power structures, gender stereotyping and an ethic of care linked to marriage and motherhood (Deem & Gilroy, 1998;Henderson & Allen, 1991), they are also capable of resisting these normalizing discourses (Foucault, 1980;Rojek, 1989;Wearing, 1998).…”
Section: Ltpa and Resistancementioning
confidence: 99%
“…Women, tbey say, depend more beavily on tbe non-productive spbere of consumption and leisure as a source of some autonomy and sense of individual identity (Wearing 1990a). During tbe early cbildrearing years, for example, leisure space for motbers of young cbildren bas been sbown to be linked to a sense of well-being, individual autonomy and identity (Wimbusb 1988;Wearing 1990bWearing , 1990c. Feminist analysis bas also rewritten tbe notion of identity; Butler (1990) in a radical re-writing of tbe perennial sociological debate on agency and structure questions tbe binary opposition of tbe two concepts claiming tbere is no T wbicb expresses an inner identity.…”
Section: And Idratity In Adtdescencementioning
confidence: 99%
“…With the progression of feminist research in the late 1990s, there has been a shift in thinking towards a feminist post-structuralist Foucauldian (1983) power analysis of leisure (Shaw 1994;Wearing, 1990Wearing, , 1998Wearing and Wearing, 1988). This feminized perspective views leisure as a self-constructed "heterotopic" space where women and men can empower themselves to negotiate and resist power structures in society (Wearing, 1998).…”
Section: Introductionmentioning
confidence: 96%
“…Since a condition of Foucault's power analysis requires relative freedom, leisure as a self-constructed "heterotopic" space is a realm where women and men can exercise power and control by negotiating and resisting structural forces. That is, leisure as a space for relative freedom allows women to deconstruct institutionalized power structures and resist structural forces (Shaw, 1994;Wearing, 1990). Seemingly, a feminist post-structural Foucauldian power analysis views women as powerful change agents who have the ability to exercise power and control to achieve increasing freedom of choice in their leisure lives.…”
Section: Introductionmentioning
confidence: 97%